Comparison of proinsulin to C-peptide ratio in children with and without type 1 diabetes and its relation to age - Benjamin R. Ellison; Jeffrey H. Burton; Daniel S. Hsia (Korean Society of Pediatric Endocrinology, 2020)
Purpose This study aimed to compare the proinsulin to C-peptide (PI:C) ratio in those with recent-onset type 1 diabetes versus those with no diabetes and to explore the effect of age on PI:C ratio. Methods Nineteen participants (n=9 with type 1 diabetes and n=10 with no diabetes) between 10 and 19 years of age were enrolled in a single-visit cross-sectional study and underwent blood collection after 10 hours fasting to measure proinsulin and C-peptide levels as well as other glycemic parameters. Results The median PI:C ratio was significantly different between type 1 diabetes and nondiabetes groups (6.24% vs. 1.46%, P<0.01). A significant negative correlation was seen between PI:C ratio and patient age after adjustment for duration of diabetes (r2 =0.61, P=0.02) in the type 1 diabetes group. Conclusions Even in this narrow age window, a higher degree of β-cell dysfunction indicated by a higher PI:C ratio was seen in younger children.